Evaluation of cardiovascular toxicity of the atezolizumab and bevacizumab combination - Takahiro Niimura; Takahiro Niimura; Mitsuhiro Goda; Mitsuhiro Goda; Koji Miyata; Jun Matsumoto; Toshihiko Yoshioka; Toshihiko Yoshioka; Hirofumi Hamano; Hirofumi Hamano; Fuka Aizawa; Fuka Aizawa; et al. (Frontiers Media S.A., 2023)
Introduction: The combination of atezolizumab, an immune checkpoint inhibitor (ICI), and bevacizumab, a vascular endothelial growth factor (VEGF) inhibitor, is the first choice for systemic therapy in hepatocellular carcinoma. Immune-related cardiovascular toxicity-myocarditis and pericarditis-are known to occur during ICI treatment. By contrast, VEGF inhibitors (VEGFIs) cause cardiovascular complications such as hypertension and heart failure. Thus, different cardiovascular toxicities have been recognized for ICIs and VEGFIs, but the impact of their combination remains unclear. Here, we aimed to investigate the cardiovascular toxicity profile of atezolizumab in combination with bevacizumab using the World Health Organization adverse event reporting database-VigiBase.Methods: We analyzed data included in VigiBase till December 2022. To evaluate the frequency of reports related to atezolizumab, bevacizumab, and their combinations for 21 adverse events, we calculated the reporting odds ratio and information component. Analyses of the fatality of various cardiovascular toxicities associated with the use of each drug were performed.Results: The database included 84,951, 10,595, and 2,092 reports of treatment with bevacizumab, atezolizumab, and their combination, respectively. The disproportionality signal of hypertension, arterial embolism and thrombosis, supraventricular tachyarrhythmias, heart failure, myocarditis, hemorrhage-related clinical events, venous embolism and thrombosis, cardiomyopathy, respiratory failure with combination regimen of atezolizumab and bevacizumab was detected. Signals of these adverse events were also detected treatment with either atezolizumab or bevacizumab alone. Venous embolism and thrombosis exhibited the highest fatality rate in the two drug combination (12.82%) relative to those of atezolizumab (6.19%) and bevacizumab (4.54%).Discussion: Cardiovascular toxicity, owing to the combination of atezolizumab and bevacizumab, was similar to that of each single agent, and no new safety concerns were observed. Caution should be exercised when combining the two drugs since the fatality rate of thromboembolism increases with combination treatment.